2023
DOI: 10.14814/phy2.15687
|View full text |Cite
|
Sign up to set email alerts
|

Fructose‐induced salt‐sensitive blood pressure differentially affects sympathetically mediated aortic stiffness in male and female Sprague‐Dawley rats

Abstract: Hypertension is the leading risk factor for major adverse cardiovascular events (MACE). Aortic stiffness and sympathoexcitation are robust predictors of MACE. Combined high fructose and sodium intake increases arterial pressure, aortic stiffness, renin, and sympathetic nerve activity in male rats. We hypothesized that activation of the renin angiotensin system (RAS) and/or the sympathetic system mediates aortic stiffness in rats with fructose‐induced salt‐sensitive blood pressure. Male and female Sprague‐Dawle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 81 publications
(130 reference statements)
2
5
0
Order By: Relevance
“…In fact, since the advent of HFCS in the 1970s, this has been the primary component of sugar used by the food industry in North America [ 28 ]. Indeed, pre-clinical work showed that even a short-term moderate increase in dietary fructose causes salt-sensitive blood pressure, diastolic dysfunction, and increased aortic PWV in rats [ 29 , 30 , 31 , 32 ]. Additionally, other rodent models showed that the increased ingestion of fructose and salt during early age (i.e., equivalent to adolescence in humans), contributes to hypertension, vascular stiffness, and a decrease in glomerular filtration rate (GFR) later in life even after the exposure to fructose and salt had been removed and later re-introduced to rats once they were older (i.e., equivalent to mid-life in humans) [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, since the advent of HFCS in the 1970s, this has been the primary component of sugar used by the food industry in North America [ 28 ]. Indeed, pre-clinical work showed that even a short-term moderate increase in dietary fructose causes salt-sensitive blood pressure, diastolic dysfunction, and increased aortic PWV in rats [ 29 , 30 , 31 , 32 ]. Additionally, other rodent models showed that the increased ingestion of fructose and salt during early age (i.e., equivalent to adolescence in humans), contributes to hypertension, vascular stiffness, and a decrease in glomerular filtration rate (GFR) later in life even after the exposure to fructose and salt had been removed and later re-introduced to rats once they were older (i.e., equivalent to mid-life in humans) [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, others have reported that females are protected from the cardiovascular effects of dietary fructose. 56 There are at least 3 possible explanations for the discrepancy. First, the diets were significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…Second, their rats were obtained from Harlan, while ours were from Charles River, and Sprague-Dawley rats from different sources have been shown to have different BPs 57 and different responses to environmental stimuli. 58 Finally, BP was measured under different conditions, that is, isoflurane anesthesia, 56 which may have impacted BP 59 versus awake animals.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, our search for studies in human subjects was only able to identify controlled studies reporting the acute effects of acute fructose ingestion (several hours). In contrast, animal studies showing deleterious effects on hemodynamics have largely assessed the long-term effects (weeks to months) of fructose on blood pressure [ 44 , 45 , 46 , 47 ], with some animal studies using dietary amounts exceeding what is typically ingested by people [ 36 , 37 , 38 , 39 ]. We identified only a limited number of publications reporting the direct effects of fructose on blood pressure in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, these changes occur despite normal blood glucose levels in the fructose-fed rats and do not elevate blood glucose levels [ 12 , 91 ]; however, insulin resistance was evident despite euglycemia [ 11 , 18 , 90 ]. Furthermore, a fructose-rich diet is associated with increased aortic stiffness in both rats [ 47 , 90 ] and humans [ 92 ]. Aortic stiffness is now recognized as a significant risk factor for cardiovascular disease and mortality [ 93 , 94 ].…”
Section: Discussionmentioning
confidence: 99%